Isotope hydrochemistry of the lakes in Schirmacher Oasis, East Antarctica - Gopinath, G.; Resmi, T. R.; Praveenbabu, M.; Pragath, M.; P.S., Sunil; Rawat, R. (My University, 2020)
The study aims to find out the ionic and isotopic compositions of some lakes in the Schirmacher Oasis in east Antarctica. The water samples were collected from 12 lakes near the Indian Antarctic station, Maitri. The chemistry of lake water indicates contribution from glacial melt water and lithology of the area. Evaporation from shallow lakes was also found to be controlling the lake water chemistry. The isotopic concentration of the lake waters also indicated input from the melt water from adjacent glaciers. δD varied between -167.2 ‰ and -250.2 ‰ and δ18O from -18.0 ‰ to -31.2 ‰. It was found that diffusion controlled kinetic effect at the liquid-ice interface for different water isotopologues and evaporative enrichment of heavier isotopes from open water bodies determined the slope of the regression line of the lake water.
Keywords: Ionic composition; Polar lakes; Schirmacher Oases; Stable isotopes